The Antiplatelet Aggregation Effect of Extract And Ethyl Acetate Fraction of Velvet Bean Seed (Mucuna pruriens L.) in Dyslipidemic Rat - Wahyu Widowati; Hana Ratnawati; Udju Djunaedi Rusdi; Wahyu Winarno; Felix Kasim (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Cardiovascular disease (CVD) is the first cause of death in the world, CVD has complex and multifactorial process including atherogenic lipoprotein, oxidized low density lipoprotein (LDL), endothelial dysfunction, plaque stability, vascular inflammation, thrombotic and fibrinolytic disorder, exercises and genetic factor. Inhibiting the platelet ag- gregation is one of the CVD prevention. Velvet bean seed (Mucuna pruriens L.) can be found abundantly in Indonesia, but has not been used as herbal medicine. Ethanol extract and ethyl acetate of velvet bean seed contain high flavonoids and antioxidants properties which is expected could inhibit platelet aggregation. The objectives of the research were to determine the activity of ethanol extract and ethyl acetate fraction of velvet bean seed towards clotting and bleeding time in dyslipidemic rats. This research used completely randomized design in dyslipidemic rats which were given by ethanol extract of velvet bean seed at the concentrations of 50, 100 and 200 mg/kg BW/day and ethyl acetate fraction of velvet bean seed at the concentrations of 15, 30 and 60 mg/kg BW/day and 42.2 mg/kg BW/day aspirin for ten days. Clotting and bleeding time were measured at days 0, 10, and 20. Data were analyzed using One way analysis of vari- ance and continued with Duncan’s post Hoc test with 95 % level of significancy. The results showed that administration of 60 mg/kg BW/day ethyl acetate fraction of velvet bean seed and at the concentrations of 100 and 200 mg/kg BW/ day ethanol extract of velvet bean seed, prolong the clotting time at day 10, ethyl acetate fraction at the concentration of 60 mg/kg BW/day, 200 mg/kg BW/day ethanol extract of velvet bean prolong bleeding time at day 10.